2019
DOI: 10.1111/hdi.12788
|View full text |Cite
|
Sign up to set email alerts
|

Does subjective assessment of dialyzer appearance reflect dialyzer performance in online hemodiafiltration?

Abstract: Introduction: In post-dilution online hemodiafiltration, a very thin balance subsists in preventing coagulation of the extracorporeal circuit (ECC) during treatment and bleeding in the patient, concerning dialyzer status and anticoagulation dose.The aim of this study was to assess whether there are clinical outcome differences between the visual aspect of the dialyzer's status in terms of clotted fibers at end of dialysis treatments, singlepool urea kinetic modeling (spKt/V) and substitution volume (SubsVol).M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Fazendeiro Matos et al showed that the cleaner the filters were at the end of dialysis, the greater the dialysis adequacy with that type of filter. The aforementioned study also concluded that the more unfractionated heparin (UFH) was used, the less likely it was to form clots (18). According to this relationship, it might be concluded that a higher amount of UFH is required to reduce the possibility of blood clotting in new filters.…”
Section: Discussionmentioning
confidence: 99%
“…Fazendeiro Matos et al showed that the cleaner the filters were at the end of dialysis, the greater the dialysis adequacy with that type of filter. The aforementioned study also concluded that the more unfractionated heparin (UFH) was used, the less likely it was to form clots (18). According to this relationship, it might be concluded that a higher amount of UFH is required to reduce the possibility of blood clotting in new filters.…”
Section: Discussionmentioning
confidence: 99%
“…During the dialysis sessions, no infusions were given through the ECC. The dialyzer effect on coagulation activation was evaluated by calculating the absolute and percentage change of serum TAT levels and by visual inspection of the dialyzer status after the end of the session (Table 2), as described by Fazendeiro et al [14]. The grades of dialyzer status were assigned after consensus by two nephrologists.…”
Section: Methodsmentioning
confidence: 99%
“…"Blood rest" is defined as a visual aspect of clotted or bloodstreaked fibers at the end of dialysis treatments after blood return. 11 To quantify the blood rest, the individual aspects of the dialyzers were compared to a set of 5 illustrations with an increasing amount of schematic blood rest, with 1 depicting the least and 5 depicting the highest amount of blood rest (Figure 2). Assessment was performed for FX-series at mid-week sessions during weeks 1 and 2, and Clearum filters at weeks 1, 3, and 6.…”
Section: Evaluation Of Visual Blood Restmentioning
confidence: 99%